2013
DOI: 10.1093/jpids/pit024
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Disclosure of HIV Status to HIV-Infected Children in Western Kenya

Abstract: Rates of informing children in western Kenya of their HIV status are low, even among older children. Guiding families through developmentally appropriate disclosure processes should be a key facet of long-term pediatric HIV management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 30 publications
9
32
1
Order By: Relevance
“…Early disclosure is more appropriate than immediate and unplanned disclosure upon entrance into the adult clinic, and also helps to reduce HIV transmission [9]. The prevalence of pediatric HIV disclosure to infected children varies widely throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Early disclosure is more appropriate than immediate and unplanned disclosure upon entrance into the adult clinic, and also helps to reduce HIV transmission [9]. The prevalence of pediatric HIV disclosure to infected children varies widely throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Disclosure of diagnosis to HIV-infected children and adolescents is a challenge worldwide (Turissini et al, 2013;Wiener, Mellins, Marhefka, & Haven, 2007) and is frequently postponed due to allegations of child's immaturity, fears that the child may tell others and feelings of guilt for having infected the child (Guerra & Seidl, 2009). In most cases, events such as schooling, drafting into the military, beginning of working careers or debut of sexual life trigger the process of (un)-planned disclosure:…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, adolescents frequently do not receive information about their diagnosis/status, although paediatric guidelines emphasise the importance of this process (Brasil, 2009; Committee on Pediatric AIDS, 1999; Programa Estadual DST/Aids CRT DST/Aids-SP, 2008; Turissini et al, 2013;Wiener et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…HIV disclosure studies in SSA have centered on telling infected children about their own HIV statuses (Bikaako-Kajura et al, 2006;Brown et al, 2011;Kallem et al, 2011;Menon et al, 2007;Moodley et al, 2006;Vaz et al, 2010;Vreeman et al, 2014); a few have focused on telling children about their parents' HIV statuses (Madiba & Matlala, 2012;Nam et al, 2009;Palin et al, 2009;Rochat et al, 2013;Rwemisisi et al, 2007). Recent studies on disclosure to HIV-positive children have revealed HIV disclosure rates between 11% and 26% in Kenya (John-Stewart et al, 2013;Turissini et al, 2013;Vreeman et al, 2014) and between 17% and 40% in other SSA countries (Biadgilign et al, 2011;Bikaako-Kajura et al, 2006;-Fetzer et al, 2011;Kallem et al, 2011;Madiba, 2012;Menon et al, 2007). Research suggests that the typical age ranges of HIV-positive children receiving full disclosure of their own HIV statuses was between 3 and 19 years in Kenya (Vreeman et al, 2014); 8 and 18 years in the Democratic Republic of Congo (Vaz et al, 2010;Vaz et al, 2008); and 5 and 15 years in South Africa (Heeren et al, 2012;Moodley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%